Consumer Attitudes towards the Causes of Food Waste in Poland - Urszula SAMOTYJA; Magdalena ANKIEL (Communications of International Proceedings, 2020)
Consumers attitudes toward food waste, which is an emerging challenge around the world, are affected by several factors and mechanisms. Recognizing them is key in order to implement effective preventive actions. The main aim of the study was identification, analysis and evaluation of consumer behavior on the food market in the context of wastage in households in Poland. The research method used was a direct individual questionnaire interview. The surveyed population constituted of consumers purchasing food products (N = 1145). The main cause of food waste (51%) is shopping without proper planning, which causes consumers to buy too many food products that are not consumed by the expiry date. The perception of excessive needs is also pointed out as a significant cause of food waste during shopping (37%). Moreover, consumers say that food waste is favorable when there is so-called ‘buying just in case’, which also leads to an excessive amount of food in households that is ultimately not consumed (23%). In the opinion of consumers in Poland, buying large packages of products also contributes to throwing away food (due to the unavailability of smaller packages or the economic benefits resulting from large capacity, 22%). The phenomenon of food waste (due to non-consumption) is obvious and acceptable to 11.2% of the Polish consumers. This study was supported by the National Science Centre (Narodowe Centrum Nauki), Poland [grant number 2017/27/B/HS4/00805].
Keywords: Consumer Behavior; Purchase Decisions; Food Waste; Decision making; Consumer attitudes; Sustainability; Malnutrition